Analisis Beban Administrasi Terhadap Pelayanan Publik pada Program Pelayanan Terpadu Satu Pintu (PTSP) di DPMPTSP Provinsi Jawa Tengah - Sarifudin, Faisal; Sijabat, Tama Amelia Putri (Idarotuna : Journal of Administrative Science, 2023)
One Stop Integrated Service is an effort to simplify public services designed by the Government to improve the quality of services to the community. The purpose of this program is to be effective in encouraging investment because it involves many potentials owned by Central Java Province. People still often express complaints related to licensing services, such as expensive fees, lack of transparency, and difficulties in procedures. This is called administrative burden. Administrative burden is any form of policy that is considered burdensome to the community in terms of public services. This research aims to describe, examine, and analyze the successful implementation of a one-stop integrated service system in Central Java Province along with the factors that support and hinder its implementation. The research method applied is a qualitative approach using a descriptive approach to achieve the research objectives. The results of the analysis show that the DPMPTSP of Central Java Province shows maximum results in quality public services because it can be proven by the positive response of the community and the implementation of services in accordance with applicable regulations.